2015
DOI: 10.1111/bph.13255
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of exogenous nitrite in postoperative ileus

Abstract: BACKGROUND AND PURPOSEAs the pathogenesis of postoperative ileus (POI) involves inflammation and oxidative stress, comparable to ischaemia/reperfusion injury which can be ameliorated with nitrite, we investigated whether nitrite can protect against POI and explored the mechanisms involved. EXPERIMENTAL APPROACHWe used intestinal manipulation (IM) of the small intestine to induce POI in C57BL/6J mice. Sodium nitrite (48 nmol) was administered intravenously just before IM. Intestinal transit was assessed using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
4
12
0
Order By: Relevance
“…This local molecular inflammatory response is followed by a cellular inflammatory phase with the recruitment of circulatory leukocytes into the muscularis and subsequent release of more pro‐inflammatory mediators . As reported previously for the murine model of POI, the inflammatory response when manipulating the murine small intestine was also confirmed in the present study. When measured at 3, 6, and 24 hours after IM, the influx of neutrophils progressively increased with the highest value at 24 hours while the intestinal level of the inflammatory cytokine IL‐6 peaked already at 3 hours after manipulation and then decreased, still being significantly enhanced at 24 hours.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This local molecular inflammatory response is followed by a cellular inflammatory phase with the recruitment of circulatory leukocytes into the muscularis and subsequent release of more pro‐inflammatory mediators . As reported previously for the murine model of POI, the inflammatory response when manipulating the murine small intestine was also confirmed in the present study. When measured at 3, 6, and 24 hours after IM, the influx of neutrophils progressively increased with the highest value at 24 hours while the intestinal level of the inflammatory cytokine IL‐6 peaked already at 3 hours after manipulation and then decreased, still being significantly enhanced at 24 hours.…”
Section: Discussionsupporting
confidence: 89%
“…When measured at 3, 6, and 24 hours after IM, the influx of neutrophils progressively increased with the highest value at 24 hours while the intestinal level of the inflammatory cytokine IL‐6 peaked already at 3 hours after manipulation and then decreased, still being significantly enhanced at 24 hours. The same time‐dependent induction pattern of IL‐6 protein/mRNA expression and MPO activity after IM is observed in other studies …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…On the other hand, we previously suggested that NO‐mediated oxidative stress rather than the cGMP pathway could decrease c‐Kit‐positive ICC networks during inflammatory condition. Some reports have indicated that oxidative stress participates in POI . We found that lower concentration of NO donor inhibited pacemaker activity but did not disrupt c‐Kit‐positive ICC network.…”
Section: Discussionmentioning
confidence: 44%